Reees's manufacturing industry (1819-20) : - Rees, Abraham (David & Charles Reprints, 1972)
Abraham Rees's monumental Cyclopaedia, which appeared in parts between 1802 and 1819, was one of the first works of its kind to be published in English which gave more than a passing reference to con-temporary industry and technology. This new printing provides in five volumes, in the original alphabetical form, the articcles on manufacturing industry. This volume covers eighty-three subjects from Montgomeryshire to Silver, and in-cludes sections of plates inllustrating Oil Mill, Paper Mill, Planing, Plated Manufac-ture, Porter Brewery, Pottery, Press, Pressure, Printing, and Silk Munufacture...